Pemenuhan Hak Konsumen atas Informasi yang Benar (Studi Kasus Tas Branded di Batam) - Shecar, Viana; Andryawan, Andryawan (UNES Law Review, 2023)
One consumer right that is no less important is the right to choose. When choosing a product, consumers are often influenced by several considerations, for example price and brand. Price and brand tend to dominate, many consumers will be tempted to buy goods at BM because brands offer low prices. This research aims to finds and analyze legal protection for consumers regarding the circulation of branded bags that are not accompanied by official documents (for example the case of the circulation of branded bags in Batam), as well as to find out and analyze the Government's efforts or supervision from the Government to minimize circulation of branded bags that are not accompanied by official documents (example is the case of the circulation of branded bags in Batam). The type of this research is normative law in descriptive analytical. The data collection technique used is studying legal material literature which includes primary legal material, secondary legal material and non-legal material. The data analysis method is qualitative analysis. The research results shows that the practice of buying and selling branded bags in Batam violates consumer protection law because it does not provide a product certificate as an official document from the manufacturer to demonstrate the authenticity of the product. Therefore, the practice of buying and selling branded bags in Batam does not fulfill the right to correct information for consumers.